Analisis Du Pont System dalam Menilai Kinerja Keuangan pada Perusahaan Manufaktur Sub Sektor Semen Periode 2017 – 2019 - Muhammad Yasir Anhar; Anessa Musfitria; Rofiqoh El Nabila (Journal of Academia Perspectives, 2022)
The purpose of this study is to assess the financial performance of cement manufacturing companies in the sub-sector. The type of research used is descriptive quantitative, which explains the data in the form of numbers or numeric then explained using words with this research method with quantitative descriptive, data collection techniques in the form of data collection by means of documentation. The sample selection was done by purposive sampling, while the sample consisted of 4 companies. For the variables used are net profit margin, total assets turnover, return on investment. The results of the analysis of the financial performance of the cement sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. A good net profit margin value is 19.6% based on the average, while the average total asset turnover value is 1.55x, and a good return on investment value is seen from the average, which is 12.23%. The cement sub-sector manufacturing company listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period that has good financial performance is PT Indocement Tunggal Prakarsa Tbk (INTP), while PT Semen Baturaja (Persero) Tbk (SMBR) has the worst financial performance. than other companies